Case Report on “Budd Chiari Syndrome” - Mercy Joseph; Vaishali Tembhare (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Hepatic Vein Thrombosisis also known as Budd Chiari Syndrome is a sparse disordermarked by obstruction and narrowing of the hepatic veins i.e., veins of the liver. 70% casers of Budd ChiariSyndrome are unknown. Approximately 10% have polycythemia vera which is a type of blood cancer.Clinical manifestations can be developed due to the blockage of the major veins which carries blood fromthe liver to the heart. Features may include hepatomegaly (an abnormally enlarged liver), pain in the upperright part of the abdomen, yellowish color of the skin and sclera (whites of the eyes) jaundice i.e., due tojaundice, ascites i.e., accumulation of fluid in the peritoneal cavity between the two layers of membranethat lines the stomach. Portal hypertension (due to increase in pressure of the portal veins) etc. Diagnosisof hepatic vein thrombosis is made based upon a detailed diagnostic findings, a thorough history of patient,and a variety of specialized tests. Management of hepatic vein thrombosis includes corticosteroid drug.anticoagulants, angioplasty, etc. Patient history: The patient is a female, 46 years old who was admittedin A.V.B.R.H. on 29/11/19 with chief complaints of tenderness in abdomen on palpation, fever, rigor andpain. Past history: Patient is a known case of hypertension and cerebrovascular accident. Clinical findings:The patient has undergone venography, Complete blood count, etc. Pharmacology: The patient was treatedwith medications such as, tab. Augmentin 625 mg, tab. Pantop 40 mg, tab. Ultracet 50 mg, tab. Mucomix625 mg. Nursing management: Administered IV fluids as advised by physician. Administered medicationsas prescribed by physician. Monitored vital signs. Conclusion: The 46 years old female was admittedto AVBRH in Cathlab ICU with chief complaints of pain in abdomen, fever, rigor etc. after undergoinginvestigations she was diagnosed as Budd Chiari Syndrome.